Vignettes: a data collection technique to handle the differential operation of items in surveys - Antonio Sergio Silva; Wilerson Lucas Campos-Silva; Maria Aparecida Gouvea; Milton Carlos Farina (BBR: Brazilian Business Review)
Vignettes are scenarios used in many areas of academic research, whose main application is related to situations in which judgments about people are subject to biases or distortions. Despite the wide use of vignettes in surveys, the recommendations for their creation are limited in the literature. Thus, this study aims to review and describe criteria presented in the literature for robust textualization of vignettes. This study presents a literature review on the use of vignettes and describes a minimum set of criteria (plausibility, clarity, simplicity, content validity and analogy between the vignette and the construct) for the judicious application of this methodology. They have presented four vignettes constructed from the literature review and validated by panel of experts, with the purpose of capturing the perception of respondents on the protagonists’ actions in scenarios about co-creation value in a health service. In this way, the study conceives the essential elements for the development of this methodology.